Autonomous Mobile Robot Following Human (Software Movement Part) - Tam , You Wei (UTeM, 2009)

(untitled)
This project will discuss on how to give command to a mobile robot to follow a human movement by using Matlab. An initial study will be done on the serial port communication and the method to control the mobile robot. This project is started by establishing a wireless communication between the serial transmitter and the soccer robot with user manual [2] instruction to configure the hardware setting. Then the software reverse engineering is applied on the soccer robot test program by using the free serial port monitor software to obtain the output data of the soccer robot test program for analysis, and then the algorithm to control the mobile robot is identified. After that, this project continue with program design and development to create an algorithm to control the degree of turning of the robot with respect to PWM value, where the PWM value is for controlling the motor speed. Next, a new program is created to control the mobile robot movement using the Matlab with algorithm obtained from software reverse engineering and program design and development. At the end of the project, the control program is combined with the vision program for the mobile robot to follow a human movement automatically after the human coordinated has been identified.